2022
DOI: 10.1021/acsami.2c10667
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Coating for Stabilizing Li Metal Batteries

Abstract: With plenty of charges and rich functional groups, bovine serum albumin (BSA) protein provides effective transport for multiple metallic ions inside blood vessels. Inspired by the unique ionic transport function, we develop a BSA protein coating to stabilize Li anode, regulate Li+ transport, and resolve the Li dendrite growth for Li metal batteries (LMBs). The experimental and simulation studies demonstrate that the coating has strong interactions with Li metal, increases the wetting with electrolyte, reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…It was this robust inorganic solid electrolyte interphase film that artificially covered the lithium metal, prohibiting undesirable side reactions on anode’s surfaces of lithium metal batteries . In addition, organic polymeric ingredients attributing to bovine serum albumin contributed to the flexibility of solid-state electrolyte interphase films so that a bovine serum albumin-inspired artificial protein was applied on lithium metal surfaces (Figure d), in order to lower anode/electrolyte interfacial stress in lithium plating/stripping process . Learning from hydrophobic qualities of natural species, scaly artificial anode/electrolyte interfaces containing small organic molecular layers were functionalized by decylphosphonate groups.…”
Section: Principles Of Bioinspired Interfaces Designing For Renewable...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was this robust inorganic solid electrolyte interphase film that artificially covered the lithium metal, prohibiting undesirable side reactions on anode’s surfaces of lithium metal batteries . In addition, organic polymeric ingredients attributing to bovine serum albumin contributed to the flexibility of solid-state electrolyte interphase films so that a bovine serum albumin-inspired artificial protein was applied on lithium metal surfaces (Figure d), in order to lower anode/electrolyte interfacial stress in lithium plating/stripping process . Learning from hydrophobic qualities of natural species, scaly artificial anode/electrolyte interfaces containing small organic molecular layers were functionalized by decylphosphonate groups.…”
Section: Principles Of Bioinspired Interfaces Designing For Renewable...mentioning
confidence: 99%
“…17 In addition, organic polymeric ingredients attributing to bovine serum albumin contributed to the flexibility of solid-state electrolyte interphase films so that a bovine serum albumininspired artificial protein was applied on lithium metal surfaces (Figure 2d), in order to lower anode/electrolyte interfacial stress in lithium plating/stripping process. 18 Learning from hydrophobic qualities of natural species, scaly artificial anode/ electrolyte interfaces containing small organic molecular layers were functionalized by decylphosphonate groups. Such interfaces were constructed onto lithium metal anodes' surfaces of lithium−sulfur batteries to repel polysulfides dissolved in electrolytes far away from lithium metal anodes via polysulfiphobic properties induced by long alkyl chains of the decylphosphonate groups.…”
Section: Principles Of Bioinspired Interfaces Designing For Renewable...mentioning
confidence: 99%
“…Using organic films or coatings on the flat surface of the inorganics has accelerated the advancement in many areas, also outside of biomedicine. It includes protection and exploration of such materials as steel and copper, electrocatalysts ( Yu et al, 2019 ), batteries ( Li et al, 2018b ; Wang et al, 2022 ) to advanced materials like sensors ( Nugroho et al, 2018 ), wearable and flexible devices ( Shim et al, 2008 ), marine ships, and aerospace vehicles ( Mann, 2009 ; Huang et al, 2014a ; Xu et al, 2021 ). Lee et al (2007) reported polymer coatings synthesized from dopamine, which could coat virtually all types of material surfaces.…”
Section: Inorganic Surfaces Functionalized By Organic Moleculesmentioning
confidence: 99%
“…Reproduced with permission. [ 122 ] Copyright 2022, Royal Society of Chemistry. f) Schematic illustration of the configuration of the SSE/Li–metal interphase with and without SPF.…”
Section: Electrode Surface/interphase Modificationsmentioning
confidence: 99%